Two Papers on Pharmaceuticals in Developing Countries - Segall, Malcolm; Barker, C. E. (Brighton : Institute of Development Studies at the University of Sussex, 1976)
This paper is intended to provide some medical background to the questions that arise over pharmaceuticals and to put these questions into a broader framework of health planning. To some extent it seeks to counter-balance a tendency to assume that the drugs in current use in many developing countries are more or less 'needed', and that the main problem is how to obtain them cheaply and self-reliantly. Therefore,this paper, takes a mainly normative approach, attempting to point to the goals towards which a rational pharmaceuticals policy could be directed.
Cover title.
Bibliography: p. 15-16.
ne 5/04/2018
Loan
Keywords: Pharmaceutical Policy; Health Planning